The Demographic and Clinical Presentation of Ulcerative Keratitis in HIV and non-HIV Infected Patients at Muhimbili National Hospita (Tanzania Medical Journal, 2015)
Background: Ulcerative keratitis and subsequent corneal scarring is at present the leading cause of ocular morbidity and unilateral blindness in developing countries. In developed countries, HIV infection has been associated with severe ulcerative keratitis. The demographic and clinical presentation of Ulcerative keratitis among HIV and non HIV infected patients are largely undetermined in Dar-es-Salaam. Objective: To compare the demographic and clinical presentation of ulcerative keratitis in HIV and Non-HIV infected patients at Muhimbili National Hospital (MNH), Dar-es-Salaam. Methodology: A comparative, hospital based cross sectional study was conducted from June 2008 - May 2009 at MNH eye department. Patients with ulcerative keratitis consecutively underwent ocular history, examination, corneal scrapping and HIV screening. Treatment was initiated based on clinical appearance of the ulcer and was changed accordingly after laboratory results. Patients were followed up until complete healing occurred. The demographic data from patients and the clinical presentation of ulcerative keratitis among HIV and non-HIV infected patients were compared. Data were analyzed using EPI Info 6 software. Results: One hundred and eighty six patients were enrolled during the study period. Of these 60% (111/186) had HIV infection (p=0.004). Compared to Non HIV -infected patients, HIV infected patients were likely to be males (p=0.0002) cohabiting or single (p=0.0001) and petty traders (P=0.0004). The leading cause of ulcerative keratitis among HIV and non-HIV infected patients were fungal and bacterial infections respectively. Compared to ulcers among non-HIV infected patients, ulcers among HIV infected patients presented with severe clinical signs and complications (p=0.47) and patients were more likely to be blind on presentation (p=0.001) and on discharge from hospital (p=0.001). Conclusion and recommendation: About 60% of patients presenting to MNH with ulcerative keratitis are infected with HIV. Compared to that in Non-HIV infected patients, ulcerative keratitis in HIV infected patients were due to fungus, presented with severe clinical signs and ended up with permanent visual loss. Efforts to screen all patients presenting with ulcerative keratitis at MNH should be instituted alongside awareness creation among health workers and the general public on the importance of seeking early treatment for ulcerative keratitis.